Addressing energy challenges: sustainable nano-ceramic electrolytes for solid-state lithium batteries by green chemistry - Chava, Sai Raghuveer; Luckett, Robert; Bashir, Sajid (Frontiers in Materials, 2025)
The escalating demand for high-performance, safe energy storage devices has propelled the advancement of solid-state battery (SSB) technology. SSBs can supplant traditional liquid electrolyte-based Li-ion batteries by offering higher theoretical capacities and enhanced safety through solid-state electrolytes. However, challenges like dendritic lithium growth and inadequate solid-solid interfaces impede their practical application. This study aims to overcome these barriers by enhancing the ionic conductivity of ceramic-based solid-state electrolytes by incorporating nanoscale multicomponent halides. Utilizing green chemistry principles, we synthesized composite electrolytes based on Li₃InCl₆, doped with fluorine (F), cerium (Ce), and molybdenum (Mo). Among these, the F-, Ce-, and Mo-doped Li₃InCl₆ electrolytes contributed uniquely to enhancing ionic conductivity. Mo-doping improved most substantially, reaching an average ionic conductivity modal value of 0.30 S cm⁻1 (Rangle 0.15,0.46) S cm−1;± 0.13 S cm⁻1, comparable to commercial liquid electrolytes. F doping enhanced lattice stability and facilitated Li⁺ ion mobility, while Ce doping improved structural integrity and reduced interfacial resistance. Comprehensive structural characterization confirmed the successful incorporation of dopants and favorable modification of the crystal lattice, facilitating enhanced Li⁺ ion mobility. Electrochemical performance evaluations using symmetrical half-cells demonstrated reduced charge transfer resistance and improved cycling stability, particularly in the Mo-doped variants. These findings underscore the effectiveness of molybdenum doping in mitigating interfacial resistance and promoting reliable ion transport in SSBs. Toxicity assessments revealed that using water as a solvent and natural extracts minimized the environmental footprint, aligning with sustainable synthesis practices. Our green nano-engineering approach not only advances the performance of solid-state electrolytes but also aligns with sustainable synthesis practices, paving the way for developing efficient and eco-friendly energy storage solutions. Additionally, our green nano-engineering approach was evaluated against traditional synthesis methods, demonstrating a 40% reduction in energy consumption and a 75% decrease in hazardous waste generation. This manuscript highlights the pivotal role of doped Li₃InCl₆ electrolytes in addressing current limitations of SSB technology, thereby contributing to the future of safe and high-capacity energy storage systems.